Адміністративно-правові засади превентивної діяльності Національної поліції України : автореферат дисертації - Парханов, Г. Р.; Parkhanov, H. R. (Київ, 2019)
Дисертацію присвячено визначенню сутності та особливостей адміністративно-правових засад превентивної діяльності Національної поліції України. Сформульовано значення, окреслено принципи та особливості превентивної діяльності Національної поліції України. Визначено адміністративно-правовий статус Національної поліції України як суб’єкта здійснення превентивної діяльності, розкрито його елементи та особливості. Особливу увагу приділено розкриттю специфіки здійснення превентивної діяльності дільничними офіцерами поліції. Охарактеризовано превентивну роботу поліції у сфері дозвільної системи. Сформульовано особливості здійснення превентивної роботи у сфері забезпечення безпеки дорожнього руху. З’ясовано зміст превентивної діяльності поліції з ювенальної превенції. Охарактеризовано зарубіжний досвід здійснення превентивної діяльності органами правопорядку та можливість його адаптації в діяльність Національної поліції України, а також сформульовано пропозиції, спрямовані на удосконалення правового та організаційного забезпечення адміністративно-правового механізму здійснення превентивної діяльності Національної поліції України.

The dissertation is focused on determining the essence and specific features of administrative and legal principles of preventive activity of the National Police of Ukraine. The author of the qualification scientific work, based on the analysis of existing theoretical points of view, has offered updated understanding of the essence and specific features of implementing preventive activities carried out by the agencies and units of the National Police as the object of administrative and legal research. The author has formulated the meaning, has outlined the principles and peculiarities of preventive activity of the National Police of Ukraine. The administrative and legal status of the National Police of Ukraine as the subject of preventive activity has been defined; its elements and features have been revealed. The legal principles of preventive activity of the National Police of Ukraine have been studied; and the place of administrative and legal regulation among them has been determined. This made it possible to offer concrete amendments to the current legislation in terms of procedural application of preventive police measures. Particular attention has been emphasized on revealing the specifics of the implementation of preventive activities by community policing officers. The preventive work of the police in the field of licensing system has been characterized. Specific features of carrying out preventive work in the field of ensuring traffic safety have been formulated. The content of preventive police activity on juvenile prevention has been clarified. The author has characterized international experience of carrying out preventive activities by law enforcement agencies and the possibility of its adaptation into the activities of the National Police of Ukraine. The author has also formulated propositions aimed at improving the legal and organizational provision of administrative and legal mechanism for the implementation of preventive activities of the National Police of Ukraine.

Диссертация посвящена определению сущности и особенностей административно-правовых основ превентивной деятельности Национальной полиции Украины. Определен административно-правовой статус Национальной полиции Украины как субъекта осуществления превентивной деятельности, а так же раскрыты его элементы и особенности. Особое внимание уделено раскрытию особенностей осуществления превентивной деятельности участковыми офицерами полиции. Охарактеризована превентивная работа полиции в сфере разрешительной системы. Сформулированы особенности осуществления превентивной работы в сфере обеспечения безопасности дорожного движения. Выяснены содержание и специфические черты превентивной деятельности полиции в сфере ювенальной превенции. Охарактеризован зарубежный опыт осуществления превентивной деятельности органами правопорядка и возможность его адаптации в деятельность Национальной полиции Украины, а также сформулированы предложения, направленные на совершенствование правового и организационного обеспечения административно-правового механизма осуществления превентивной деятельности Национальной полиции Украины.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Administrative and Legal Principles of Preventive Activity of the National Police of Ukraine
Keywords: Україна; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.07; адміністративно-правові засади; administrative and legal principles; административно-правовые основы; превентивна діяльність; preventive activity; превентивная деятельность; Національна поліція України; National Police of Ukraine; Национальная полиция Украины; правовий статус; legal status; правовой статус; ювенальна превенція; juvenile prevention; ювенальная превенция; безпека дорожнього руху; road safety; безопасность дорожного движения; дозвільна система; permission system; разрешительная система